The dying kingdom - Sullivan, Steven D.; Rams, Vinod (Renton, WA : Wizards of the Coast ; [New York, N.Y.] : Distributed in the United States by Holtzbrinck Pub, 2004)
Nearra and the Scarlet Brethren have blundered into a terrifying plot in the kingdom of Arngrim that could cost her and all her friends their lives.
"Mirror Stone."
Ages 10 and up.
Accelerated Reader AR
Keywords: Wizards -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy; Fantasy fiction